Gentry, Caron E., Laura J. Shepherd, and Laura Sjoberg, eds. 2019. The Routledge Handbook of Gender and Security. Routledge, 440 pp, £ 190 (Hardback) - Stosic, Milena (Journal of Regional Security, 2022)
Gender equality represents one of the primary predictors of peace and an important global sustainable development goal. Simultaneously, it can be used to legitimize wagging war and foreign interventions. Mainstream IR scholarship seldom takes gender into account, although there is a body of evidence suggesting that gender is of the core security aspects, specially through answering what counts as security and whose security matters. As Laura Sjoberg notices, gender was absent from key periodicals in security studies, such as the journal Security Studies that started publishing the terms women and gender only around mid-2000s. This handbook uses feminist lenses to advance comprehensive analysis in security studies and to scrutinize and inform policies serving social justice. To that end, this volume will be useful to students, scholars and practitioners in the field, curious to dig beneath the mainstream IR and uncover how gendered power relations work in the complex context of security and global politics.